2014
DOI: 10.7547/0003-0538-104.5.455
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Tendinopathy

Abstract: To date, studies have examined various intrinsic and extrinsic risk factors implicated in the etiology of PTT. The interaction of these factors with an individual's genetic background may provide valuable data and help offer a more complete risk profile for PTT. A properly constructed genetic association study to determine the genetic basis of PTT would provide a novel and alternative approach to understanding this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…[8] The etiology of PTTD is likely to be multifactorial because both extrinsic such as ankle surgery and intrinsic risk factors have been reported. [9] PTTD is more frequent in hypertensive, obese, and rheumatic patients with peak incidence at the age of fifties; in addition, it is 3 times more common in females. [10] In our case, hypertension, rheumatoid arthritis, and overweight were considered as adverse factors in the development of PTTD.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The etiology of PTTD is likely to be multifactorial because both extrinsic such as ankle surgery and intrinsic risk factors have been reported. [9] PTTD is more frequent in hypertensive, obese, and rheumatic patients with peak incidence at the age of fifties; in addition, it is 3 times more common in females. [10] In our case, hypertension, rheumatoid arthritis, and overweight were considered as adverse factors in the development of PTTD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence was estimated to be 3%, the figure was believed to be underestimated because it was frequently undiagnosed (Neville et al, 2016). PTT is not necessarily symptomatic, otherwise associates with a board spectrum of generalized medical problems and pain that overlooks until secondary complaints emerged (Beeson, 2014;Bluman et al, 2007;Kohls-Gatzoulis et al, 2004). Deland et al (2005) demonstrated that PTT is difficult to diagnose radiographically and could be noticed until ligaments are damaged.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to investigate or determine the biomechanics of PTT onset. The majority of research pertained to clinical description and management (Beeson, 2014). The interaction between different intrinsic and extrinsic factors was identified as the risk factors (Beeson, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations